Tenapanor: new approach to counter irritable bowel syndrome with constipation - Brashier, D. B. S.; Kumar, Ajay; Singh, Anuj; Pratap, Uday (International Journal of Basic & Clinical Pharmacology, 2020)
Irritable bowel syndrome (IBS) is a functional gastrointestinal disorder chronic in nature and characterized predominantly by abdominal pain or discomfort associated with altered bowel habits, diagnosis requires characteristic symptoms during the last 3 months and onset ≥6 months ago. Symptom-based approaches for functional bloating, constipation and diarrhea are best utilised to identify IBS. IBS with constipation exerts significant impairment on work productivity by hampering quality of life. Inadequate relief by existing modalities, persistent hard stools and visceral abdominal pain demanded further clinical research. Tenanapor a novel molecule acts locally on gastrointestinal sodium/hydrogen exchanger isoform 3 (NHE3), an antiporter a counter transporter and exert antinociceptive effects on visceral sensation thereby decreases the frequency of abdominal pain. Action on NHE3 receptors located on small intestine and colon’s apical surface reduces the absorption of sodium and phosphate, with minimal systemic exposure. NHE3 Inhibition induced sodium absorption results in increase in water secretion into intestinal lumen resultant an accelerated intestinal transit time and softer stool consistency. Most common adverse reactions (≥2%) are diarrhea, abdominal distension, flatulence and dizziness. The drug is metabolised mainly by CYP3A4/5 and excreted in feaces (70%) and urine (7%). Tenapanor’s minimal systemic absorption is likely to be associated with a relatively inert safety and tolerability profile. Based on positive results from the phase III T3MPO trial program, tenapanor demonstrated promising results for IBS-C management and received US Food and Drug Administration approval as IBSRELA @ Ardelyx Pharma in September 2019 and augment existing modalities for management of IBS-C.